Make it in America - Liveris, Andrew
The case for revolutionizing the U.S. economy, from a leading CEO America used to define itself by the things we built. We designed and produced the world's most important innovations, and in doing so, created a vibrant manufacturing sector that established the middle class. We manufactured our way to the top and became the undisputed economic leader of the world. But over the last several decades, and especially in the last ten years, the sector that was America's great pride has eroded, costing us millions of jobs and putting our long-term prosperity at risk. Now, as we struggle to recover from the worst recession in generations, our only chance to turn things around is to revive the American manufacturing sector and to revolutionize it